Maic Audo Lin Sihombing - Maic Audo Lin Sihombing; Sutiman B. Sumitro; Muhaimin Rifa'i (Journal of Experimental Life Science)
Diabetes mellitus is one of the common metabolic disorders with increasing prevalence during recent years with hyperglycemia as its characteristic. DM has been shown to be a state of free radicals over production resulted from hyperglycemia that can activate cellular signaling pathways transcription of factor NF-κB which stimulates the production of several inflammatory mediators andl lead to chronic inflammation. Chronic inflammation is implicated in β-cell damage and function and promotes apoptosis. EMSA Eritin is a polyherbal consisting of soy bean extracts, coconut water extract and red rice extract that assumed to be antidiabetic and anti-inflammatory. This study will assess the effectiveness of EMSA Eritin against inflammation in diabetes mellitus by measuring levels of NF-κB produced by immunocompetent cells in DM mice model. Streptozotocin 100 mg.kg-1 BW is used to induce diabetes mellitus in mice. Oral administration of EMSA Eritin was given for 14 days with dose of 0.3125 mg.g-1 BW, 3.125 mg.g-1 BW and 31.25 mg.g-1 BW. Data were analyzed using One-way ANOVA (p<0.05) and Duncan test using SPSS 16.0 for Windows. The results showed that EMSA Eritin can be used as an alternative therapy for the treatment of DM. The level of NF-κB in diabetic mice significantly decreased when the mice received EMSA Eritin.